2020
DOI: 10.1080/09273948.2019.1699122
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Topical Medication in Patients with Inflammatory Eye Disease

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document.When citing, please reference the published version. Take down policyWhile the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Patient compliance with treatment and follow-up appointments is associated with better results. 43,44 Identifying factors that limit compliance are essential to optimize treatment and develop strategies that will enhance compliance with treatment and regular monitoring. 45 The patient's immune profile is a substantial parameter for the management of uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Patient compliance with treatment and follow-up appointments is associated with better results. 43,44 Identifying factors that limit compliance are essential to optimize treatment and develop strategies that will enhance compliance with treatment and regular monitoring. 45 The patient's immune profile is a substantial parameter for the management of uveitis.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient follows a personalised journey along the dry eye disease care pathway tailored to disease severity, underlying pathophysiology, therapeutic success rates, locally available dry eye disease services, professional opinions, waiting lists and patient choice. Achieving good adherence to treatments in dry eye disease is a well-recognised challenge and also impacts the patient journey along this care pathway [ 26 ]. Figure 1 provides an example NHS dry eye disease care pathway and illustrates the frequency of appointments and multiple treatment trials to optimise patients’ symptoms and signs.…”
Section: The Nhs Dry Eye Disease Care Pathwaymentioning
confidence: 99%
“…The OSDI score is calculated as the mean of the responses of all of the questions answered by the respondent, which is then multiplied by 25, to give a score in the range 0-100, with higher scores representing more severe symptomatology. Based on the resulting scores, patients can be classified as having normal (OSDI=0-12), mild (13)(14)(15)(16)(17)(18)(19)(20)(21)(22), moderate (23)(24)(25)(26)(27)(28)(29)(30)(31)(32) or severe (33+) symptomatology. As mentioned above, while the OSDI was intended for use in OSD, a patient involvement group indicated that many of the questions were applicable to uveitis because of the similarity of presenting symptoms and how these affect daily activities.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…17 Recent studies confirm that neuropathic ocular pain specifically is not only prevalent in those with dry eye disease (DED) but also correlates with DED severity and persistence. [18][19][20][21][22] From a patient perspective, a lack of understanding of their condition may inhibit treatment adherence, 23 perpetuating both physical and mental morbidities. 5 A lack of understanding of IED on the behalf of a patient's social contacts may also have an additional impact.…”
Section: Introductionmentioning
confidence: 99%